Pengaruh Self-Efficacy dan Kerja Sama Tim Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening pada Puskesmas Andalas Kota Padang - Silvani Latiessa; Marta Widian Sari; Ai Elis Karlinda (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The study aims to determine the extent of the influence of Self-Efficacy and Team Work on Employee Performance through Job Satisfacatin as an intervening variable at Andalas Community Health Center, Padang City. The sampling method used saturated sampling, with a sample of 54 respondents. The data analysis method used is the Structural Equation Modeling (SEM) the analysis using the Partial Least Square (SmartPLS). The results of this study concluded that, (1) Self-Efficacy has a significant effect on Job Satisfaction at Andalas Community Health Center, Padang City, (2) Team Work has a significant efffect on Job Satisfaction at Andalas Community Health Center, Padang City, (3) Self-Efficacy does not have a significant effect on Employee Performance at Andalas Community Health Center, Padang City, (4) Team Work has a significant influence on Employee Performance at the Andalas Community Health Center, Padang City, (5) Job Satisfaction has a significant influence on Employee Performance at the Andalas Community Health Center, Padang City, (6) Self-Efficacy has a significant influence on Employee Performance through Job Satisfaction at the Andalas Community Health Center, Padang City, (7) Team Work has a significant influence on Employee Performance through Job Satisfaction at the Andalas Community Health Center, Padang City.